Отстрел невест: роман / Андрей Белянин - Белянин Андрей Олегович (Армада, 2003)
Экземпляры: ф.14 (2003) / Инвентарный номер: 47091 / Цена: / Сис.шифр: 84(2Рос=Рус)6-445 / Авт.знак: Б 44 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-445^VLBC/RL